Intercultural Communication of Political Issues on Twitter Platform: Cyber Discourse Analysis - Romi Artika, Mutiara; Sofilla, Devi; Simorangkir, Raslima; Wulandari, Vanny; Nisa, Khairun; Putri, Dian Marisha (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study aims to identify how high-context and low-context communication is represented in Twitter posts and to analyze the differences in communication styles between the two countries, particularly in the context of high-context and low-context communication using Edward Hall’s theory. The method in this research is qualitative design with the data are three tweets related about #KawalPutusanMK and about new American presidential election. The result in this research highlights cultural differences in tweets, with Indonesians using indirect, context-dependent language reflecting collectivism, while Americans favor direct, explicit communication reflecting individualism. These patterns underscore the need to understand cultural values to enhance cross-cultural online interactions.